White spruce enrichment planting in boreal mixedwoods as influenced by localized site preparation: 11-year update - Myriam Delmaire; Nelson Thiffault; Evelyne Thiffault; Julie Bouliane (The Forestry Chronicle, 2020)
Ecosystem-based management aims to maintain the natural proportion of native species over a given landscape. White spruce (Picea glauca (Moench) Voss) is a species sensitive to environmental conditions; it is especially demanding in terms of nutrients and its regeneration is negatively affected by clearcut harvesting. Its proportion is now significantly lower than what it was in the preindustrial forests of Québec (Canada). As a native species in boreal Québec, efforts to maintain its proportion in the landscape are undertaken for white spruce, but little is known about the best practices to maximize establishment success of seedlings planted in the balsam fir (Abies balsamea)–white birch (Betula papyrifera) bioclimatic domain. Our general objective was to identify planting practices as related to microsite treatment that favour white spruce sapling survival and size after 11 growing seasons following enrichment planting of sites harvested by mechanized careful logging in an ecosystem-based management context. We also aimed at comparing white spruce performance with that of black spruce (Picea mariana (Mill.) BSP), a native species that is less sensitive to abiotic stress. Finally, we wanted to assess stand composition at this juvenile stage, as a function of microsite treatment and planted species. Localized site preparation did not significantly affect growth or survival for white spruce compared to control conditions. Furthermore, localized site preparation did not increase the proportion of white and black spruce, as evaluated by basal area. Our results suggest that white spruce can be successfully established in enrichment planting in fir-dominated boreal forests, without site preparation.